In Silico Study of Thioguanine Derivatives as Hemopexin Matrix Metalloproteinase9 (PEX-9) Inhibitors - Kevin Cahaya Putra; Ervan Setyo Nugroho; Yohanes Krisna Wisnumurti; Sangga Putra Dewa; Benedictus Wisnu Putra Jati; Reynaldo Tiara; Dewi Setyaningsih; Maywan Hariono (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Matrix Metalloproteinase (MMP) was broadly studied as one of the protein targets in stopping angiogenesis. The most common target in MMP, i.e., the catalytic site, is reported as being the non-selective target for inhibition amongst all MMPs, but its inhibition is associated with adverse side effects. Hemopexin in MMP9 (PEX9) was found to be different to the other domains in the MMP family, which could be the next target for anticancer due to the availability of its crystal structure in the protein data bank (pdb). In this study, we design the analogues of a compound from the ZINC database bearing a pyrimidinone scaffold which previously showed activity as a PEX9 inhibitor using molecular docking. The docking is carried out using Autodock 4.0 with parameters such as 250 run and lammarckian genetic algorithm. The result shows that six designed compounds have a free energy of binding from -7.0 to -11.0 kcal/mol. The important amino acid residues which are involved in the hydrogen bond interaction are ARG106, GLU60, GLU14, and GLN154. In conclusion, the six design compounds could give an insight mechanism to inhibit the PEX-9 activity in silico.Keywords: Docking, Hemopexin, MMP9, PEX9, Thioguanine